Labour Market Performance and Start-up Costs: OECD Evidence - Paloma Lopez-Garcia (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper is intended to make a contribution to the empirical literature explaining the rise of unemployment since the 1970s in western economies by means of interactions between shocks and institutions. The contribution is twofold. First, the impact of a general feature of developed economies that has been surprisingly neglected in the literature is analyzed, namely, the employment shift from industry and agriculture to services. The second contribution of the paper is the focus on the interaction of that shock with the administrative burdens on firm creation. The working hypotheses is that countries that impose high costs on the creation of new companies are not able to create enough jobs in the service sector to successfully absorb the workers released from the agriculture and industry sector. The result is higher unemployment.
Keywords: 330; macroeconomics of unemployment; panel data; start-up costs